Game-Based Nawatobi Learning to Improve Students’ Agility in Elementary Physical Education - Erit Triana; Akmal Quvondiqov; Baxodir Madaminov (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to improve students’ agility through the implementation of game-based Nawatobi learning in elementary physical education. It focuses on enhancing student participation and motor skill development by applying a structured and engaging learning approach in classroom settings. Methodology: This study used classroom action research with two cycles involving 26 sixth-grade students. Data were collected using observation sheets, questionnaires, and agility performance tests. Instruments included structured observation forms and student response questionnaires. Data were analyzed using descriptive qualitative techniques and percentage calculations to measure learning activity and improvement outcomes. Main Findings: The findings show a significant improvement in students’ agility and participation from the initial condition to Cycle I and Cycle II. Student activity, motivation, and engagement increased substantially. Most students achieved higher agility performance levels, indicating that the implementation of game-based Nawatobi learning effectively enhanced both motor skills and learning participation. Novelty/Originality of this study: This study introduces a structured integration of Nawatobi as a game-based learning approach specifically targeting agility development. It combines motor skill assessment with student engagement analysis within a classroom action research framework, providing a practical and context-based model for improving physical education learning in elementary schools.